Analysis Of Water Use Efficiency in Antokan Irrigation - Atyka Trianisa; Siti Septiani Rullyah; Wiwi Sartika (CV. HEI PUBLISHING INDONESIA, 2025)
Water plays a crucial role in agricultural productivity and food security, particularly in irrigated rice farming systems. However, seasonal water shortages and inefficient water management often reduce crop yields in several irrigation areas. This study aimed to evaluate irrigation water use efficiency in the Antokan Irrigation Area, Nagari Manggopoh, Agam Regency, West Sumatra, to support more effective water management strategies. The evaluation was conducted through field measurements of irrigation discharge and channel efficiency, combined with calculations of irrigation water requirements based on consumptive use, land preparation needs, percolation losses, and effective rainfall. Water balance analysis was also applied to assess the adequacy of water supply. The results showed that water availability in the Namuang Saiyo irrigation channel reached 0.061 m³/s, while the total irrigation water requirement was 0.051 m³/s. The irrigation channel efficiency was 94.81%, indicating good hydraulic performance and minimal conveyance losses. The overall irrigation water use efficiency reached 83.29%, classified as efficient. These findings indicate that the Antokan irrigation system is capable of meeting crop water requirements optimally and can serve as a reference for improving irrigation management in similar agricultural areas.